Spraint density of the Eurasian otter (Lutra lutra) is an accurate indicator of its population status in urban areas - Jooseong Kim; Sungwon Hong (Environmental and Sustainability Indicators)
The most traditional method used to monitor the distribution of otters is spraint density surveys, but there has been long-standing debate regarding whether this approach is sufficiently accurate. In response to this debate, the effectiveness and reliability of spraint density surveys as a method for assessing the otter distribution within urban areas were evaluated by comparing their results with those achieved using two alternative methods: genetic analysis and camera trap-based density based on the random encounter model. In addition, the spraint density was tested as an indicator of otter habitat preferences by modeling 19 environmental factors (seven associated with prey, nine with land use, and three with the river environment) using a pcount model. Spraint surveys, genetic analysis, and camera trapping were conducted at 36, 22, and 12 sites within Daegu Metropolitan City, respectively. A regression model indicated that the spraint density was strongly associated with the other two methods, while it was also found to accurately represent otter habitat preferences, with otters in urban areas preferring sites with a high density of large fish and river islets. Consequently, spraint density surveys were the most time-effective, cost-effective, and reliable method for investigating the otter distribution in this urban environment. As a result, population status assessment using spraint density surveys can provide important information for the conservation management of urban otters.